2010
DOI: 10.1111/j.1365-2443.2010.01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ATPase activities as a primary defect of mutant valosin‐containing proteins that cause inclusion body myopathy associated with Paget disease of bone and frontotemporal dementia

Abstract: Valosin‐containing protein (VCP) has been shown to colocalize with abnormal protein aggregates, such as nuclear inclusions of Huntington disease and Machado‐Joseph disease, Lewy bodies in Parkinson disease. Several mis‐sense mutations in the human VCP gene have been identified in patients suffering inclusion body myopathy associated with Paget disease of bone and frontotemporal dementia (IBMPFD). Recently, we have shown that VCP possesses both aggregate‐forming and aggregate‐clearing activities. Here, we showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 36 publications
7
108
1
Order By: Relevance
“…4B), corroborating previous observations (19,20,22). We noticed that the enhancement in ATPase activity is not uniform across all IBMPFD mutants.…”
Section: Intra-and Intersubunit Regulation Of P97-previous Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…4B), corroborating previous observations (19,20,22). We noticed that the enhancement in ATPase activity is not uniform across all IBMPFD mutants.…”
Section: Intra-and Intersubunit Regulation Of P97-previous Studiessupporting
confidence: 82%
“…Although some reports have shown that pathogenic mutants have ATPase activities similar to that of the wild type (6,21), others have demonstrated significantly enhanced ATPase activity (19,20,22). No mechanistic interpretation has been offered in the latter reports as to why the ATPase activity is elevated.…”
Section: Data Collectionmentioning
confidence: 57%
See 1 more Smart Citation
“…Due to an altered inter-subunit communication in IBMPFD mutants the D1 domains fail to regulate their respective nucleotide-binding states as evidenced by a lower amount of pre-bound ADP and weaker affinity for ADP, resulting in a better accessibility for ATP in comparison to the wild-type protein [29,30]. The altered conformational equilibrium of the N domain in p97 disease mutants is accompanied by elevated ATPase activities in vitro [43,115,116] and altered interactions with some but not all cofactors in cells, which has been proposed to be key to the pathogenesis of IBMPFD [10,[116][117][118] (for a recent review see [119]). Specifically, increased amounts of p47, UFD1-NPL4, and ataxin-3, but decreased amounts of UBXD1 and UBE4B have been found.…”
Section: Nucleotide-dependent Control Of Cofactor Interactionsmentioning
confidence: 99%
“…In 2004 and 2010, VCP mutations were identifi ed that are causative for IBMPFD (inclusion body myopathy associated with Paget disease of bone and frontotemporal dementia) [ 5 ], a human hereditary disease with dementia, and for rare cases of familial amyotrophic lateral sclerosis (ALS) [ 6 ], respectively. In our evaluation, all tested pathogenic VCPs showed signifi cant elevations of the ATPase activities, as compared with wild-type VCP [ 7 ], and thus we proposed the possibility that the constitutive elevation of its ATPase activity is a pathogenic mechanism.…”
Section: Vcp In Neurodegenerative Disordersmentioning
confidence: 97%